UNDERSTANDING FLOW OF CARBON AND NITROGEN IN MALAYSIAN SANITARY LANDFILL - MS., Venu Mahendra; M., Mohd Afzanizam; P., Agamuthu (Malaysian Journal of Science, 2013)
Landfill can be an artificial carbon sink; accumulates and stores carbon-containing chemical compound for an indefinite period. Landfill posed risks of undesired environmental impacts due to the generation of leachate and gases namely carbon dioxide, CO2 and methane, CH4 with trace amounts of nonmethane organic compounds (NMOC) that include air pollutants and volatile organic compounds. Elements were selected based on environmental matrix and importance as raw materials with definite negative effects. In 2009, Jeram Sanitary Landfill received 730,547.79 metric tonne of waste from Kuala Lumpur and Selangor municipalities. Jeram Sanitary Landfill (JSL), as located in area of tropical country receives high amount of precipitation, about 1900mm to 2000mm, contributing to significant intrusion of acid deposition such as carbon monoxide, CO and nitrogen oxides, NOx. The quantity of leachate generated reflects the performance of landfill based on water balance components which include surface runoff, evapotranspiration, lateral drainage and leachate generated. Material Flow Analysis was realised using quantified possible inputs and outputs in elementary level. Kitchen waste and garden waste contributes significantly to the mass flow in landfill, indirectly contrubuting to source of organic carbon and total nitrogen in landfill. Carbon was predominantly exported in gas form whereas for nitrogen, the major pool was found in the atmosphere. The atmospheric pool of nitrogen was found coupled to the biogeochemical cycle, influenced by microbial nitrogen fixation and denitrification. (Keywords: landfill, carbon, nitrogen, material flow analysis, waste)